Biocompatibility, bone healing, and safety evaluation in rabbits with an IlluminOss bone stabilization system. Issue 10 (20th February 2017) - McSweeney, Amanda L.; Zani, Brett G.; Baird, Rose; Stanley, James R. L.; Hayward, Alison; Markham, Peter M.; Kopia, Gregory A.; Edelman, Elazer R.; Rabiner, Robert
ABSTRACT: Bone healing, biocompatibility, and safety employing the IlluminOss System (IS), comprised of an inflatable balloon filled with photopolymerizable liquid monomer, was evaluated in New Zealand white rabbits. Successful bone healing and callus remodeling over 6 months was demonstrated radiologically and histologically with IS implants in fenestrated femoral cortices. Biocompatibility was demonstrated with IS implants in brushed, flushed femoral intramedullary spaces, eliciting no adverse, local, or systemic responses and with similar biocompatibility to K‐wires in contralateral femurs up to 1 year post‐implant. Lastly simulated clinical failures demonstrated the safety of IS implants up to 1 year in the presence of liquid or polymerized polymer within the intramedullary space. Polymerized material displayed cortical bone and vasculature effects comparable to mechanical disruption of the endosteum. In the clinically unlikely scenario with no remediation or polymerization, a high dose monomer injection resulted in marked necrosis of cortical bone, as well as associated vasculature, endosteum, and bone marrow. Overall, when polymerized and hardened within bone intramedullary spaces, this light curable monomer system may provide a safe and effective method for fracture stabilization. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2181–2190, 2017. Abstract : The IlluminOss system employs an inflatable balloon infused with a photopolymerizable liquid monomer that was utilized within the femoral intramedullary spaces of NZW rabbits and evaluated for bone healing, biocompatibility, and safety. When polymerized and hardened within bone intramedullary spaces, this system may provide a safe and effective method for fracture stabilization.